Formation of legal competence of women suffering from domestic violence by means of non-formal education - Rutyan, Lesya (Social work and education, 2022)
The scientific achievements of scientists on ways to prevent domestic violence are summarized. Theoretical analysis of scientific works concerning the process of formation of legal competence of victims of domestic violence is carried out. The way of formation of legal competence of victims of domestic violence is proposed - non-formal education. The structure of legal competence of victims of violence is singled out, which consists of the following components: motivational-value, semantic and activity. The essence of each component of domestic violence in the process of obtaining non-formal education is revealed. The peculiarities of non-formal education in the process of formation of legal competence of victims of domestic violence are described. It is noted that the legal competence of victims of domestic violence is a process of forming the ability to effectively use in their activities legislative and other normative legal acts regulating their protection, security and freedom; at the level of non-formal education - the formation of legal competence of victims of domestic violence in the process of psychological assistance, as a result of the process of rehabilitation, counseling and clarification on the implementation of the provisions of regulations. It is concluded that the integration of non-formal education in people's lives is designed to optimally combine and implement the formation of legal competence in victims of domestic violence.